Fluid-solid coupling model and biological features of large vestibular aqueduct syndrome - Chen, Zewen; Luo, Mengjie; Zhou, Can; Bie, Xu; Yu, Shen; Sun, Xiuzhen (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The computed tomography (CT) images of the temporal bone of large vestibular aqueduct syndrome (LVAS) patients are used to establish 3D numerical models based on the structure of the inner ear, and these are used to construct inner ear fluid-structure coupling models. The physiological features and pathogenesis of LVAS are analyzed from a biomechanical perspective using finite element analysis. Methods: CT images of the temporal bone were collected from five children attending the Second Hospital of Dalian Medical University in 2022. The CT images were used to build 3D models of the inner ear containing the vestibular aqueduct (VA) by Mimics and Geomagic software, and round membrane models and fluid-structure coupling models were built by ANSYS software to perform fluid-structure coupling analysis. Results: By applying different pressure loads, the deformation of the round membranes occurred, and their trend was basically the same as that of the load. The deformation and stresses of the round membranes increased with the increase of load; under the same load, the deformation and stresses of the round membranes increased with the expansion of the width of the VA midpoint. Conclusion: CT images of the temporal bone used clinically could establish a complete 3D numerical model of the inner ear containing VA; fluctuations in cerebrospinal fluid pressure could affect inner ear pressure; and VA had a limiting effect on the pressure from cerebrospinal fluid, and the larger the VA, the smaller the limiting effect on the pressure.